Poverty and Inequality in Chile: Methodological Issues and a Literature Review - Georgina Pizzolitto (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2005)
This paper has two main objectives. On the one hand, it is aimed at assessing the reliability of poverty and inequality measures in Chile, and their robustness to methodological changes. In particular, we evaluate the impact on the measurement of poverty and inequality of adjustments for non-response, missing values, under-report, implicit rent from own-housing, and regional prices. The second objective of the paper is to review the poverty and inequality literature in Chile. In particular, we focus on the contributions on the level, trends and characteristics of poverty and inequality, and the development of anti-poverty programs, highlighting the main gaps remaining in the literature.
Keywords: D3; I32; O54; 330; poverty; inequality; measurement; Chile